Checklist of the Discomycetes (Fungi) of Patagonia, Tierra del Fuego and adjacent antarctic areas - Gamundi, Irma Josefa (2004)
Information about fungi of the orders Cyttariales, Helotiales, Ostropales, Pezizales, Rhytismatalesand Thelebolales (Discomycetes) collected in Patagonia, Tierra del Fuego and adjacent antarctic areas(Patagonia), and information about their associated organisms was located, abstracted, keyboarded,edited and validated. The largest single information sources were dried reference collections in Argentinaand elsewhere, and published information as listed in this work’s bibliography. Other records werederived from fresh collections, other reference collections and field observations. Information is stored ina computerized system of relational databases for taxonomic, nomenclatural, bibliographic and biologicalobservations data. This system allows storage of parallel data in different languages, and distinguishesoriginal information from current opinion about what that information may mean. In the BiologicalRecords Database, 5029 separate records were created for observations on the spatial and temporaloccurrence of living organisms in the region. Of these 2613 were Discomycetes, with records derived asfollows: Patagonia and Tierra del Fuego (Argentina, 1854; Chile, 687); adjacent antarctic areas (72).Excluding synonyms, these Discomycetes represented 361 species and subspecific taxa (160 genera, 22families and 7 orders) the remaining records were organisms associated with these Discomycetes asfollows: 163 of animals (8 species, 8 genera, 6 families and 5 orders); 2 of chromistans; 223 of fungi (52species, 54 genera, 26 families and 13 orders); 2028 of plants (159 species, 122 genera, 59 families and 39orders). Each of these different taxa (and each known synonym) is represented by a separate record in theTaxonomic & Nomenclatural Database. Information about relevant bibliographic sources is stored inmore than 120 records in the Bibliographic Database. The databases were used to produce the presentchecklist of names given to Discomycetes observed in Patagonia. A typical entry comprises the fungusname, author(s), and information on the original place of publication of the name, together with anyknown synonyms (classification at generic level and above largely follows the 9th edition of Ainsworth &Bisby’s Dictionary of the Fungi, Kirk et al., 2001). This is followed by basic information derived from thedatabases: the number of times the fungus has been recorded from the region, the date of the earliest recordfrom the region, months in which the fungus has been observed in the region, geographical distribution bycountry (and within countries by an appropriate subnational division), associated organism andsubstrata, a list of reference collection numbers identifying preserved specimens and sometimes livingisolates of each fungus, and bibliographic citations identifying any published sources of the information.The status of each name is indicated and, where appropriate, synonyms are provided and cross-indexed.The list is accompanied by an explanatory introduction, a taxonomic index, indexes by countries andsubnational divisions of the region, by taxonomy of associated organisms and by substrata, and abibliography. No new taxa are described. Apart from four new nomenclatural combinations, no newscientific names of any sort are knowingly introduced.